2021
DOI: 10.1021/acs.jafc.1c00727
|View full text |Cite
|
Sign up to set email alerts
|

Insights in the Recalcitrance of Theasinensin A to Human Gut Microbial Degradation

Abstract: Due to low bioavailability of dietary phenolic compounds in small intestine, their metabolism by gut microbiota is gaining increasing attention. The microbial metabolism of theasinensin A (TSA), a bioactive catechin dimer found in black tea, has not been studied yet. Here, TSA was extracted and purified for in vitro fermentation by human fecal microbiota, and epigallocatechin gallate (EGCG) and procyanidin B2 (PCB2) were used for comparison. Despite the similarity in their flavan-3-ol sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Generally, the dimerization and oxidation of one of the most significant phenolic compounds in green tea, catechins, can result in the production of TFs through peroxidases, polyphenol oxidases, as well as the fermentation flow of black tea. 212,213 TFDG, among other TF groups, can be found in black tea more than other foods and drinks. On the whole, the fusion of catechol-type and pyrogallol-type B rings of epicatechin gallate (ECG) as well as epigallocatechin gallate (EGCG) makes these two compounds, i.e., ECG and EGCG, become condensed and form the TFDG.…”
Section: ■ Neurodegenerative Diseasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, the dimerization and oxidation of one of the most significant phenolic compounds in green tea, catechins, can result in the production of TFs through peroxidases, polyphenol oxidases, as well as the fermentation flow of black tea. 212,213 TFDG, among other TF groups, can be found in black tea more than other foods and drinks. On the whole, the fusion of catechol-type and pyrogallol-type B rings of epicatechin gallate (ECG) as well as epigallocatechin gallate (EGCG) makes these two compounds, i.e., ECG and EGCG, become condensed and form the TFDG.…”
Section: ■ Neurodegenerative Diseasesmentioning
confidence: 99%
“…The bioavailability of TFDG depends on the function of the gut microbiota since TFDG can be slightly absorbed in the small intestine. 212 Investigations have revealed that TFDG can undergo the gut microbiota and convert into TF, TF3′G, and TF3G. 214,215 TFs can be influenced by the gut microbiota, and following the degalloylation, they can convert into other smaller phenolic compounds, namely 3-(3′,4′-dihydroxyphenyl)propionic acid and 5-(3′,4′-dihydroxyphenyl)-γ-valerolactone.…”
Section: ■ Neurodegenerative Diseasesmentioning
confidence: 99%
See 3 more Smart Citations